2022
DOI: 10.1155/2022/2914210
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chitosan‐Assisted Fe3O4@SiO2 Magnetic Nanostructures Functionalized with Nisin as a Topical Combating System against Vancomycin‐Intermediate Staphylococcus aureus (VISA) Skin Wound Infection in Mice

Abstract: The clinical significance of vancomycin-intermediate S. aureus (VISA) infections is intensified by its tendency to develop resistance to antimicrobials and persistent infections. The decreasing effectiveness of the antimicrobials available is now seriously compromised; thus, there is an emergent need to invent new classes of antimicrobial agents that can rapidly and efficiently eradicate infections. Fe3O4@SiO2@chitosan (CS) nanocomposites were successfully synthesized and then decorated with nisin to gain Fe3O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“… 44 For Gram-negative bacteria, crowding of metal nanoparticles on the bacterial surface triggers excessive generation of Fe 3+ ions and ROS, leading to cell death. 13 Therefore, cell disruption occurred with time and the highest leakage of cytoplasmic contents was observed at 3.5 hour and also with a higher concentration ratio of nanoconjugate (N-CS-IONP (1 : 4)).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“… 44 For Gram-negative bacteria, crowding of metal nanoparticles on the bacterial surface triggers excessive generation of Fe 3+ ions and ROS, leading to cell death. 13 Therefore, cell disruption occurred with time and the highest leakage of cytoplasmic contents was observed at 3.5 hour and also with a higher concentration ratio of nanoconjugate (N-CS-IONP (1 : 4)).…”
Section: Discussionmentioning
confidence: 96%
“…The results of the study indicated that the addition of chitosan to the magnetic nanoparticles (MNPs) increased the sensitivity of the VISA strain ( S. aureus ), with chitosan-coated MNPs exhibiting up to a 2-fold reduction in both the minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) compared to free MNPs. 13 Previous research demonstrated the antimicrobial activity of chitosan, which specifically disrupts the microbial membrane while displaying no toxicity towards mammalian somatic or tumoral cells. 35 In a separate investigation, chitosan polymer exhibited high uptake by mammalian cells and specific binding to the negatively charged bacterial membrane, allowing for the targeted release of tetracycline at the desired site.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations